Nitrogen source track and associated isotopic dynamic characteristic in a complex ecosystem: A case study of a subtropical watershed, China. (May 2018) - Hao, Zhuo; Zhang, Xinyu; Gao, Yang; Xu, Zhiwei; Yang, Fengting; Wen, Xuefa; Wang, Yueming
Abstract: By identifying the main sources of nitrate (NO3 − ) can obtain useful information to support the management of NO3 − pollution, particularly in subtropical catchments with shallow drinking water wells. This study used water chemistry and dual stable isotopes δ 15 N and δ 18 O methods to assess seasonal and spatial variations of NO3 − in precipitation, surface water, and groundwater in an agricultural and forest subtropical catchment in Jiangxi Province, China. The maximum concentrations of nitrate-nitrogen (NO3 − -N) and ammonium-nitrogen (NH4 + -N) were 10.4 and 10.8 mg L −1 in samples collected from 221 rainfall events from 2011 to 2013. About 4.4% and 12.3% NH4 + -N concentrations of surface water and groundwater exceeded the thresholds of 1.0 and 0.2 mg L −1 . The NO3 − -N concentrations in surface water were closely correlated with NH4 + -N concentrations in surface water and groundwater (r = −0.71 and r = −0.71, P < 0.05). The concentrations of NH4 + -N and NO3 − -N were significantly higher in a fishery pond and nearby drinking wells than in other monitoring points. Annual exports of NO3 − -N and NH4 + -N were 4.06 × 10 4 and 8.14 × 10 3  kg yr −1, respectively and NO3 − -N is the main form of N loss. The δ 15 N values ranged from 0‰ to 20‰ in surface water and groundwater, and the δ 18 O values ranged from 0‰ to 15‰ and 1‰–13‰, respectively. Dual stable isotope natural abundance distribution and water chemistry [NO3 − ]/[Cl − ] molar ratio information suggested that manure and sewage and soil N were the main sources of NO3 − in surface water and manure and sewage in groundwater in summer and winter. In spring, water occurred denitrification and ammonium fertilizer, manure and sewage were the main sources of NO3 − in surface water and groundwater which sampling points were closer residential area and fish ponds than paddy field and local farmers used more Manure. Manure applications should be reasonable around drinking water wells to protect the drinking water quality. Graphical abstract: Image 1 Highlights: Nitrogen is mainly lost as nitrate from subtropical agro-forest catchments. Nitrate natural sources come from evaporites. Manure and sewage were major sources of nitrate in the study area. There was denitrification in surface water but not in ground water.